Mini Tinjauan Literatur Pemanfaatan Software Mathway untuk Berfikir Komputasi Siswa - Halimatussya’diyah Purba; Yahfizham Yahfizham (Lembag, 2025)
This study is a mini observation of literature that aims to examine the use of Mathway software in supporting students’ computational thinking skills during mathematics learning. The research method is Systematic Literature Review (SLR), by reviewing a number of relevant articles using Google Scholar. The results of the study indicate that the use of Mathway can help students understand the steps to solve problems systematically, improve analytical skills, problem solving, and understanding of mathematical concepts. In addition, this application is also able to increase learning motivation because it presents an interactive and interesting process. However, the use of Mathway needs to be done in a balanced way so that students do not depend entirely on the application and continue to develop understanding through other learning resources. Therefore, Mathway can function as an effective tool in learning as an improvement in students’ computational thinking skills in this digital age.